SIMANKEL: A Web-based Information System for the Efficiency of Village Administration - Muhammad Zamroni Uska; Arianti , Baiq Desi Dwi; Nafisah, Khufatun; Wirasasmita , Rasyid Hardi; Kholisho, Yosi Nur; Amri, Zaenul (Universitas Medan Area, 2025)
Administrative services in Sekarteja Village are still carried out manually through physical recording, which causes data irregularity, risk of losing archives, and limited access to information for the community. This research aims to develop and evaluate the feasibility of a web-based Kelurahan Administration Management Information System (SIMANKEL) as a solution to these problems. System development uses the Research and Development (R&D) method with a waterfall process model that includes requirements analysis, design, implementation, testing, and documentation. The system was developed using PHP Native, MySQL as a database, and the user interface was designed based on UI/UX principles using Visual Studio Code. System evaluation was conducted by referring to three aspects of the ISO 9126 software quality standard, namely functionality, usability, and efficiency. The test results show that all functions run according to specifications (100%), the usability aspect obtained a feasibility score of 91% from 20 respondents (excellent category), and the efficiency aspect shows that the system load time is in the good category based on testing using GTMetrix. These findings indicate that SIMANKEL is feasible to use as an information system for administrative services in Sekarteja Village and has the potential to increase the effectiveness, efficiency, and transparency of pub services.